The clinical features, diagnosis, treatment, and prognosis of neuroinvasive listeriosis: a multinational study - MİDİ, İPEK (SPRINGER, 2015)
The aim of this study was to determine the independent risk factors, morbidity, and mortality of central nervous system (CNS) infections caused by Listeria monocytogenes. We retrospectively evaluated 100 episodes of neuroinvasive listeriosis in a multinational study in 21 tertiary care hospitals of Turkey, France, and Italy from 1990 to 2014. The mean age of the patients was 57 years (range, 19-92 years), and 64% were males. The all-cause immunosuppression rate was 54 % (54/100). Forty-nine (49 %) patients were referred to a hospital because of the classical triad of symptoms (fever, nuchal rigidity, and altered level of consciousness). Rhombencephalitis was detected radiologically in 9 (9 %) cases. Twenty-seven (64 %) of the patients who had cranial magnetic resonance imaging (MRI) performed had findings of meningeal and parenchymal involvement. The mean delay in the initiation of specific treatment was 6.8 +/- 7 days. Empiric treatment was appropriate in 52 (52 %) patients. The mortality rate was 25 %, while neurologic sequelae occurred in 13 % of the patients. In the multivariate analysis, delay in treatment [odds ratio (OR), 1.07 [95 % confidence interval (CI), 1.01-1.16]] and seizures (OR, 3.41 [95 % CI, 1.05-11.09]) were significantly associated with mortality. Independent risk factors for neurologic sequelae were delay in treatment (OR, 1.07 [95 % CI, 1.006-1.367]) and presence of bacteremia (OR, 45.2 [95 % CI, 2.73-748.1]). Delay in the initiation of treatment of neuroinvasive listeriosis was a poor risk factor for unfavorable outcomes. Bacteremia was one of the independent risk factors for morbidity, while the presence of seizures predicted worse prognosis. Moreover, the addition of aminoglycosides to ampicillin monotherapy did not improve patients' prognosis.
Keywords: CENTRAL-NERVOUS-SYSTEM; BACTERIAL-MENINGITIS; MONOCYTOGENES MENINGITIS; ADULTS; RHOMBENCEPHALITIS; ENCEPHALITIS; MANAGEMENT; MENINGOENCEPHALITIS; INFECTION; EPISODES